1997
DOI: 10.1029/96jb03393
|View full text |Cite
|
Sign up to set email alerts
|

Velocity structure from forward modeling of the eastern ridge‐transform intersection area of the Clipperton Fracture Zone, East Pacific Rise

Abstract: Abstract. In the spring of 1994, we undertook an extensive geophysical study of the Clipperton Fracture Zone (FZ) on the fast spreading East Pacific Rise. The Clipperton Area Seismic Study to Investigate Compensation experiment (CLASSIC) included surveys to examine the deep structures associated with the fracture zone and adjacent northern ridge segment. In this paper, we report the results from five seismic profiles acquired over the eastern ridge-transform intersection (RTI), including profiles over the RTI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…In contrast, an axial reflector has not been detected beneath the ridge axis at 10º30 0 N, although the presence of a crustal low-velocity zone suggests that melt is present, possibly in a mush zone [24]. At 10º30 0 N, the crustal thickness is essentially normal (¾5.5 km [24]), despite the inferred low magma supply. On the other hand, recent studies on the EPR have shown that crustal thickness does not vary in any simple way with magma budget as inferred from ridge axis depth or cross-sectional area [29,30].…”
Section: Tectonics and Geochemistry Of The Epr At 10º30mentioning
confidence: 93%
See 3 more Smart Citations
“…In contrast, an axial reflector has not been detected beneath the ridge axis at 10º30 0 N, although the presence of a crustal low-velocity zone suggests that melt is present, possibly in a mush zone [24]. At 10º30 0 N, the crustal thickness is essentially normal (¾5.5 km [24]), despite the inferred low magma supply. On the other hand, recent studies on the EPR have shown that crustal thickness does not vary in any simple way with magma budget as inferred from ridge axis depth or cross-sectional area [29,30].…”
Section: Tectonics and Geochemistry Of The Epr At 10º30mentioning
confidence: 93%
“…Much of the EPR between 9º and 14ºN is underlain by a seismic reflecting horizon which has been interpreted as evidence for the presence of magma chambers at a depth of between 1 and 2.5 km beneath the seafloor [1]. In contrast, an axial reflector has not been detected beneath the ridge axis at 10º30 0 N, although the presence of a crustal low-velocity zone suggests that melt is present, possibly in a mush zone [24]. At 10º30 0 N, the crustal thickness is essentially normal (¾5.5 km [24]), despite the inferred low magma supply.…”
Section: Tectonics and Geochemistry Of The Epr At 10º30mentioning
confidence: 99%
See 2 more Smart Citations
“…This linear oceanic ridge separates the Huatung Basin off SE Taiwan from the oceanic crust of the West Philippine Basin (Murauchi et al 1968). Fracture zones near the Gagua Ridge, northwestward extending to the Taitung Canyon , are similar to those ridges with fracture zones in the North Atlantic (Detrick et al 1993), the South Ocean (Collot et al 1995), the Central Pacific and the East Pacific Rise (Begnaud et al 1997). The Gagua Ridge formation in the western Philippine Sea and how the Gagua Ridge relates to the origins of Huatung Basin and West Philippine Basin have been the focal points of several investigations.…”
Section: Introductionmentioning
confidence: 96%